Impact of Green Human Resource Management Practices on the Environmental Performance of Green Hotels in Turkey - Irani, Foad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
This research aims to investigate whether green hotels’ environmental performance might improve through staff environmental commitment and green process innovations. Data were obtained from a survey questionnaire conducted with employees of 409 green hotels operating in Turkey. The PLS-SEM technique was adopted using Smart-PLS software to examine the proposed hypotheses. The results verified that green human resource management (GHRM) practices produce a higher level of environmental performance when employee environmental commitment and green process innovations are deployed. Therefore, this study suggests that green hotel management should promote GHRM practices throughout their organizations to enhance employee involvement in environmentally sustainable activities. It adds particularly to a new line of study focused on understanding the essential role of GHRM practices in improving the environmental performance of green hotels.

ÖZ: Bu çalışmanın amacı, yeşil insan kaynakları yönetimi uygulamalarının, otel çevresel performansı üzerinde etkili olup olmadığını ortaya koymaktır.Yukarıdaki ilişkiye ek olarak, çalışanların çevresel bağlılığı ve yeşil süreç yeniliğinin aracılık rolü araştırılmıştır. Bu amaçla, anket oluşturulmuş ve toplamda 409 yeşil otel çalışanından anketler toplanmıştır. Toplanan veriler SmartPLS programı ile analiz edilmiştir. Çalışmanın sonuçları, yeşil insan kaynakları yönetimi uygulamalarının otel çevresel performansı ile pozitif ilişkili olduğunu göstermektedir. Ayrıca bu çalışma, çalışanların çevresel bağlılığı ve yeşil süreç yeniliğinin yeşil insan kaynakları yönetimi uygulamalarının ve otel çevresel performansı arasındaki ilişkiye aracılık ettiğini göstermiştir. Bu nedenle, bu çalışma, yeşil insan kaynakları yönetimi uygulamalarının, çalışanların çevresel bağlılığı, yeşil süreç yeniliği ve otelin sürüdürülebilir ve çevre dostu performansını artırdırğı ve bu değişkenler üzerinde öncül rol oynadığı görülmüştür. Buna ek olarak bu çalışma, yeşil insan kaynakları yönetimi uygulamalarının otel çevresel performansı üzerinde etkili olduğu ve ağırlama literatürene yeni bir kazanç olarak değerlendirilmiştir.
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2022. Supervisor: Prof. Dr. Hasan Kılıç.
Keywords: Thesis Tez; Tourism Faculty; Sustainable Tourism--Green Tourism--Turkey; GHRM practices; employee environmental commitment; green process innovation; environmental performance; green hotels; Turkey